Sample Preparation and Liquid Chromatography Mass Spectrometry Analysis of Alkylphenolic Compounds and Steroid Sex Hormones in Sediments - Mira Petrovia; Damia Barcela (The Scientific World Journal)
A new methodology, based on the use of accelerated solvent extraction (ASE) and highly selective cleanup using restricted access material (RAM) on-line coupled with liquid chromatography–mass spectrometry (LC–MS), is presented for the simultaneous and unequivocal determination of alkylphenol ethoxylates (APEOs), their degradation products and halogenated derivatives, and steroid sex hormones in sediment samples. Using the integrated RAM–LC–MS system, the simultaneous determination of alkylphenolic compounds and sex hormones was achieved, yielding recoveries higher than 60% and producing low MS background noise.